Therapeutic effectiveness of low-calorie ketogenic diet on body composition and biochemical parameters in polycystic ovary syndrome - An intervention study - Avuk, Hande Seven; Bad, Murat (Aran Ediciones, S L, 2025)
Introduction: the effectiveness of the ketogenic diet (KD) as a therapeutic approach for managing weight, hormonal, and metabolic aspects of polycystic ovary syndrome (PCOS) requires further clarification despite its growing popularity. Objectives: this study evaluated the short-term effects of a 4-week low-calorie ketogenic diet (LCKD) on body composition, biochemical, and hormonal parameters in overweight or obese women with PCOS. Methods: thirteen women with PCOS (mean age 29.77 +/- 7.54 years, median BMI 27.2 kg/m2) participated in this clinical intervention study. Body composition (bio-electrical impedance), anthropometric measurements, and biochemical/hormonal parameters were assessed pre-and post-intervention. Results: participants achieved a mean body weight loss of 6.90 % +/- 2.04 %. Significant reductions were observed in body weight, BMI, fat percentage, fat mass, fat-free mass, waist, hip, and neck circumferences, and waist-to-hip/waist-to-height ratios (p < 0.05). LCKD also led to significant decreases in fasting glucose, insulin, HOMA-IR, HDL-cholesterol, prolactin, and IGF-1 levels (p < 0.05). Conversely, sexual hormon binding globulin (SBHG) and TNF-alpha levels significantly increased (p < 0.05). Multiple regression analysis indicated that changes in waist (t = 4.196), hip (t = 3.983), and neck (t =-2.820) circumferences significantly impacted prolactin levels, while changes in fat percentage (t =-3.326, p = 0.021), fat mass (t = 3.501, p = 0.017), and hip circumference (t = 2.905, p = 0.034) influenced SHBG levels (p < 0.05). Conclusions: short-term LCKD intervention shows potential as a therapeutic dietary strategy, yielding beneficial effects on both anthropometric and key biochemical parameters in overweight or obese women with PCOS.
Keywords: Ketogenic Diet; Menstrual Dysfunction; Polycystic Ovary Syndrome; Very Low-Calorie Ketogenic Diet; Medical Nutrition Therapy